(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Bas S. V. The content of the concepts of "competence" and "competence" in the writings of modern educators. The analysis of the literature connected with the definitions of «competency» and «competence» their type and structure is proposed in this article.